E-Archive In Plaju Ulu Village Based On Web - Hartati, Eka; Irawan, Ari; Fatmariani, Fatmariani; Yunifa, Wiza (Politeknik Ganesha Medan, 2023)
Abstract:The focus of this research is to design a Web-Based E-Archive in Plaju Ulu Village for services regarding E-Archives.The system development method uses the prototype method, while the system modeling uses Data Flow Diagram. This application testing is done using black box testing, where this testing is used to see done only observe the results of execution through test data and check the functionality of the software.The results of this research produce an e-archive application, and can provide information about any archives in Plaju Ulu Village, Palembang City. The system testing technique used in this study is black box testing, this test obtains input conditions for all functional needs of the program. Based on the test results ranging from admin features, incoming mail data features, outgoing mail data features, personnel data features, incoming mail archive features, outgoing mail archive features, all results are valid or successful. Users of this e-archive application consist of services, kasi, and lurah. .Keywords: E-Archives, Data Flow Diagram, black box testing; application.